Tras Nazarín : el eco de una tierra en otra tierra - Espada, Javier; Andrés Lacasta, José Alberto (Tolocha Producciones, 2015)
A journey through memory accompanied by Buñuel's photographs taken during the scouting of locations for "Nazarín", as well as the ones made by Manuel Álvarez Bravo during the shooting of the film, along with the testimonies and reflections of artists, filmmakers and intellectuals like Luis Eduardo Aute, Jean Claude Carrière, Carlos Reygadas, Silvia Pinal, Arturo Ripsetein or Carlos Saura among many others, to re-discover the poetic, vivid and inspiring force of Buñuel's cinematography.--